Potential value of salivary ALP and LDH in early diagnosis of oropharyngeal carcinoma - XIA Zhanghui; FU Xiaohong (Kouqiang hemian waike zazhi)
[Objective:] To investigate the potential application value of salivary alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) in early diagnosis of oropharyngeal carcinoma. [Methods:] A total of 77 patients with oropharyngeal cancer (cancer group), 61 patients with benign oral tumors (benign group) and 51 healthy volunteers (control group) from January 2018 to January 2022 were selected. The levels of ALP and LDH in saliva were detected between each group, and the clinical data and pathological information were collected. The relationship between salivary ALP, LDH level and the incidence rate of oropharyngeal carcinoma, clinicopathological features of oropharyngeal carcinoma were statistically compared. [Results:] The expression levels of salivary ALP and LDH in oropharyngeal carcinoma group were higher than those of benign group and control group (P<0.001). The levels of salivary ALP and LDH in patients with low or moderate differentiation, TNM stageⅡand cervical lymph node metastasis were higher than those of patients with high differentiation, TNM stageⅠ and no cervical lymph node metastasis cases (P<0.001) . Smoking, high-risk human papilloma virus infection, oral ulcer, high levels of salivary ALP and LDH were risk factors for the incidence of oropharyngeal cancer (P<0.01). The area under the curve of salivary ALP and LDH in the diagnosis of oropharyngeal carcinoma was 0.918, which were greater than the individual diagnosis result of 0.649, 0.769 (z=5.626、3.787, P<0.05). [Conclusion:] The levels of salivary ALP and LDH in patients with oropharyngeal carcinoma are significantly increased, which are related to the occurrence of oropharyngeal carcinoma and tumor behavior. Salivary ALP and LDH level can be used as a marker for early diagnosis of oropharyngeal carcinoma.